Evaluasi Sistem Informasi Logbook Menggunakan Model Human Organization Technology (HOT) Fit - Taman Yani; Refni Wahyuni; Yesica Devis (SEULANGA SYSTEM PUBLISHER, 2022)
Logbook is an information system that is used for recording the activities of FMIPA Riau University employees and also as a media for attendance of FMIPA Riau University employees which is managed by the Personnel and IT department of the Riau University FMIPA. This study aims to test and evaluate the application of Information System Technology referring to quantitative descriptive analysis based on the HOT Fit Model's, namely Users (HR), Organizations based on the Personnel perspective of FMIPA Riau University because there are still user complaints, there has never been an evaluation of the application of the Riau University logbook using the HOT method. -FIT. This study uses 9 variables, namely system quality, information quality, service quality, system development, system use, user satisfaction, organizational structure, organizational environment and net benefits. Data collection was carried out by distributing online questionnaires to 60 people consisting of 53 assistants and 7 leaders. This research uses Structural Equation Modeling (SEM-PLS) analysis technique. The results of this study indicate that the variable using the system has the highest value, which is 0.709 or 70.9%, which means that the variable using this system is the variable that has the greatest influence on the application of the FMIPA Riau University logbook information system. Keywords: HOT-Fit, Logbook FMIPA Universtias Riau, SEM-PLS